A Meta-Analysis of Anomia Treatment in Bilingual Aphasia: Within- and Cross-Language Generalization and Predictors of the Treatment Outcomes. - Leea, Seongsil; Faroqi-Shaha, Yasmeen (Journal of Speech, Language & Hearing Research, 2024)
Purpose: The present meta-analysis investigated the efficacy of anomia treatment in bilingual and multilingual persons with aphasia (BPWAs) by assessing the magnitudes of six anomia treatment outcomes. Three of the treatment outcomes pertained to the “trained language”: improvement of trained words (treatment effect [TE]), within-language generalization of semantically related untrained words (WLG-Related), and within-language generalization of unrelated words (WLG-Unrelated). Three treatment outcomes were for the “untrained language”: improvement of translations of the trained words (crosslanguage generalization of trained words [CLG-Tx]), cross-language generalization of semantically related untrained words (CLG-Related), and crosslanguage generalization of unrelated untrained words (CLG-Unrelated). This study also examined participant- and treatment-related predictors of these treatment outcomes. Method: This study is registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the number CRD42023418147. Nine electronic databases were searched to identify word retrieval treatment studies of poststroke BPWAs of at least 6 months postonset. Pre- and posttreatment single-word naming scores were extracted for each eligible participant and used to calculate effect sizes (within-case Cohen’s d) of the six treatment outcomes. Random-effects meta-analyses were conducted to assess weighted mean effect sizes of the treatment outcomes across studies. Multiple linear regression analyses were used to examine the effects of participant-related variables (pretreatment single-word naming and comprehension representing poststroke lexical processing abilities) and treatment-related variables (type, language, and duration). The methodological quality of eligible studies and the risk of bias in this meta-analysis were assessed. Results: A total of 17 published studies with 39 BPWAs were included in the meta-analysis. The methodological quality of the included studies ranged from fair (n = 4) to good (n = 13). Anomia treatment produced a medium effect size for TE (M = 8.36) and marginally small effect sizes for WLG-Related (M = 1.63), WLG-Unrelated (M = 0.68), and CLG-Tx (M = 1.56). Effect sizes were nonsignificant for CLG-Related and CLG-Unrelated. TE was significantly larger than the other five types of treatment outcomes. TE and WLG-Related effect sizes were larger for BPWAs with milder comprehension or naming impairments and for treatments of longer duration. WLG-Unrelated was larger when BPWAs received phonological treatment than semantic and mixed treatments. The overall risk of bias in the meta-analysis was low with a potential risk of bias present in the study identification process. Conclusions: Current anomia treatment practices for bilingual speakers are efficacious in improving trained items but produce marginally small within-language generalization and cross-language generalization to translations of the trained items. These results highlight the need to provide treatment in each language of BPWAs and/or investigate other approaches to promote cross-language generalization. Furthermore, anomia treatment outcomes are influenced by BPWAs’ poststroke single-word naming and comprehension abilities as well as treatment duration and the provision of phonological treatment